Entrepreneurship paradigms cases of business ventures in Malaysia - Juhary Ali (Penerbit Universiti Utara Malaysia, 2005)
This book is dedicated to the case writers who had shown their dedication, commitment and hard work in their case writing project from March to June 2000. The cases were selected from numerous business ventures that are currently active and participate in the economy in Sarawak.